Fc-small molecule antibody mimetics - Wold, Erik D. (Bioconjug Chem, 2015)
Antibody therapeutics are a promising drug class due to their high specificity and favorable pharmacokinetics. While there are many methods for the development of antibodies specific to disease associated antigens, selecting antibodies against functional epitopes with high specificity and affinity can be difficult for certain epitopes. We describe a generalizable method for synthesizing antibody mimetics by site specifically conjugating small molecules (with high affinity and specificity to disease associated antigens) to an Fc fragment to develop drugs with the benefits of an antibody. As a proof of concept, an E269pAcPhe Fc antibody Fc fragment was produced and subsequently site-specifically labeled with a linker-modified folic acid compound to generate an Fc-folic acid antibody-mimetic. This was chosen as the model system because the high-affinity folate receptor FR-α is highly expressed in a number of cancer types including breast and ovarian cancer. The specificity of the Fc-folic acid conjugate was assessed via flowcytometry with the folate-receptor positive breast cancer cell line MDA-MB-231 by measuring Fc-folic acid binding in both the absence and presence of an excess of folic acid. Fc-small molecule conjugates could be developed into a unique class of antibody-like therapeutics.